2014
DOI: 10.5296/ije.v6i4.6322
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Predictors of Success and Satisfaction in an Online Higher Education Program in Turkey

Abstract: The aim of this study was to determine the predictors of success and satisfaction in an undergraduate distance education ELL degree program in Turkey. In this study, the independent variables are instructor support, student interaction and collaboration, personal relevance, authentic learning, active learning, and student autonomy and the dependent variables are student success and student satisfaction. The participants were 85 distance education students enrolled at the English Language and Literature Distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
1
4
0
1
Order By: Relevance
“…This issue is very important because the absence of instructor support would create substantial problems regarding distance education for the majority of students. Evidence for this is provided by Kirmizi (2014), who found a modest level of association between interaction and student collaboration, active learning, student autonomy, personal relevance, educator support and authentic learning.…”
Section: Discussionmentioning
confidence: 99%
“…This issue is very important because the absence of instructor support would create substantial problems regarding distance education for the majority of students. Evidence for this is provided by Kirmizi (2014), who found a modest level of association between interaction and student collaboration, active learning, student autonomy, personal relevance, educator support and authentic learning.…”
Section: Discussionmentioning
confidence: 99%
“…The student satisfaction is the level of happiness the student experiences to themselves from online education [ 69 ]. [ 70 ] studied on the relationship between the student satisfaction and the academic achievement and found that a positive correlation exists between the two variables. The author further elaborated that the cultural variations affect the learners' satisfactions which ultimately affects the achievement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Learning motivation is related to the student's attitude toward learning. Motivation is one of the main factors influencing the student's success [32] and comfortable learning [33]. As one of the learner's readiness aspects, motivation plays a significant role in measuring the student's academic satisfaction and achievement [32].…”
Section: Introductionmentioning
confidence: 99%
“…Motivation is one of the main factors influencing the student's success [32] and comfortable learning [33]. As one of the learner's readiness aspects, motivation plays a significant role in measuring the student's academic satisfaction and achievement [32]. Self-efficacy is the student's ability to demonstrate learning skills.…”
Section: Introductionmentioning
confidence: 99%